Gary Becker's Theory Transformed : Introducing a Lobbying Matching Market for Optimal Interest Group Representation - Tokarčíková, Alexandra; Škrabka, Martin; Čihák, Jakub; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This bachelor’s thesis is modelling behavioural patterns of agents engaged in lobbying: an interest group, a policy-maker, and a hired lobbyist. It does so by introducing theoretical concepts which describe these behaviours. Gradually, these concepts are used to create a model summarizing how agents enter a market named The Lobbying Matching Market, and how they maximize their expected utility by creating matches with each other. This model describes the workings of the lobbying market for both the US and the European Union and compares the two, shedding light on different practices and strategies. Additionally, it shows that lobbying expenses can be used to help economists better understand the intensity of preferences and collective action.
Vedoucí práce: Martin Škrabka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses